The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/poc.4496
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of graphene oxide to metal‐free phthalocyanine through hydrogen bonding for optoelectronic applications: An experimental and computational study

Abstract: This paper focuses on incorporation of graphene oxide (GO) to metal‐free phthalocyanine (MPc) through only hydrogen bonding and π‐π stacking. Briefly, Pc‐GO composites at various concentrations were prepared by self‐assembly method. The processing time was kept below 10 min to avoid covalent attachment and we aimed at answering the research question of what will happen if the conjugation is realized only through hydrogen bonding under extremely limited processing times. The as‐prepared MPc‐GO composites were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, while GO/Chol-ZnPc showed monomeric Q bands, Chol-ZnPc exhibited a doublet with absorbance maxima at about 703 nm (Q x ) and 724 nm (Q y ), suggesting aggregation of Chol-ZnPc in the solvent [67]. Upon introduction of GO, the doublet disappeared and turned into a single peak, an observation in good agreement with previous reports [37]. Further, this peak was blueshifted as compared to Q y .…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Interestingly, while GO/Chol-ZnPc showed monomeric Q bands, Chol-ZnPc exhibited a doublet with absorbance maxima at about 703 nm (Q x ) and 724 nm (Q y ), suggesting aggregation of Chol-ZnPc in the solvent [67]. Upon introduction of GO, the doublet disappeared and turned into a single peak, an observation in good agreement with previous reports [37]. Further, this peak was blueshifted as compared to Q y .…”
Section: Resultssupporting
confidence: 90%
“…However, the processing time was too limited in the present work for a covalent attachment. In addition, it could be realized that the functional groups in the present work cannot allow a hydrogen bonding, unlike the previous work of Yabas et al [37]. In fact, both the red shift and the blue shift of the Q band were reported as depending on the substituted groups in previous works where various GO and Pc derivatives were coupled at relatively similar processing conditions [42,74,75], and the blue shift of the Q y in the present work might be ascribed to π−π and electrostatic interactions between GO and Chol-ZnPc.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Saloni et al 25 reported lead-free perovskites A2BCl6 for photovoltaic applications by using DFT approach. Yabas et al 26 studied optical and electronic properties of MPc and MPc-Go composites with the help of DFT and experimental approaches. Poon et al 27 performed DFT calculations for ionomers consisting of amidinium or imidazolinium groups.…”
mentioning
confidence: 99%